Influence of cement compressive strength and porosity on augmentation performance in a model of orthopedic screw pull-out. (January 2018) - Pujari-Palmer, Michael; Robo, Celine; Persson, Cecilia; Procter, Philip; Engqvist, Håkan
Abstract: Disease and injuries that affect the skeletal system may require surgical intervention and internal fixation, i.e. orthopedic plate and screw insertion, to stabilize the injury and facilitate tissue repair. If the surrounding bone quality is poor the screws may migrate, or the bone may fail, resulting in fixation failure. While numerous studies have shown that cement augmentation of the interface between bone and implant can increase screw pull-out force, the physical properties of cement that influence pull-out force have not been investigated. The present study sought to determine how the physical properties of high strength calcium phosphate cements (hsCPCs, specifically dicalcium phosphate) affected the corresponding orthopedic screw pull-out force in urethane foam models of "healthy" and "osteoporotic" synthetic bone (Sawbones). In the simplest model, where only the bond strength between screw thread and cement (without Sawbone) was tested, the correlation between pull-out force and cement compressive strength (R 2 = 0.79) was weaker than correlation with total cement porosity (R 2 = 0.89). In open pore Sawbone that mimics "healthy" cancellous bone density the stronger cements produced higher pull-out force (50–60% increase). High strength, low porosity cements also produced higher pull-out forces (50–190% increase) in "healthy" Sawbones with cortical fixation if the failure strength of the cortical material was similar to, or greater than (a metal shell), actual cortical bone. This result is of particular clinical relevance where fixation with a metal plate implant is indicated, as the nearby metal can simulate a thicker cortical shell, thereby increasing the pull-out force of screws augmented with stronger cements. The improvement in pull-out force was apparent even at low augmentation volumes of 0.5 mL (50% increase), which suggest that in clinical situations where augmentation volume is limited the stronger, lower porosity calcium phosphate cement (CPC) may still produce a significant improvement in screw pull-out force. When the correlation strength of all the tested models were compared both cement porosity and compressive strength accurately predicted pull-out force (R 2 =1.00, R 2 =0.808), though prediction accuracy depended upon the strength of the material surrounding the Sawbone. The correlations strength was low for bone with no, or weak, cortical fixation (R 2 =0.56, 0.36). Higher strength and lower porosity CPCs also produced greater pull-out force (1–1.5 kN) than commercial CPC (0.2–0.5 kN), but lower pull-out force than PMMA (2–3 kN). The results of this study suggest that the likelihood of screw fixation failure may be reduced by selecting calcium phosphate cements with lower porosity and higher compressive strength, in patients with healthy bone mineral density and/or sufficient cortical thickness. This is of particular clinical relevance when fixation with metal plates is indicated, or where the augmentation volume is limited. Graphical abstract: Highlights: The effects of cement porosity and strength on screw pull-out were investigated. Augmentation strength was limited by the strength of surrounding bone/Sawbone. A model is proposed to predict pull-out force.